Brand engagement in self-concept (BESC), value consciousness and brand loyalty: a study of generation Z consumers in Malaysia. Issue 1 (31st March 2020) - Ismail, Ahmed Rageh; Nguyen, Bang; Chen, Junsong; Melewar, T.C.; Mohamad, Bahtiar
Abstract : Purpose: This study aims to examine the relationship between brand engagement in self-concept (BESC), value consciousness (VC) and brand loyalty among Generation Z consumers. In addition, the study aims to segment the Generation Z consumers based on BESC and VC and examine the differences between the segments. Design/methodology/approach: A self-administered questionnaire was developed and administered to a sample of 346 undergraduate students in Malaysia. The hypothesized structural models are tested using partial least squares structural equation modeling. The study also uses cluster analysis to segment the Generation Z consumers. Findings: The results reveal that among Generation Z consumers both BESC and VC have a positive effect on brand loyalty. Additionally, the mediation analysis established that BESC plays a mediating role in the relationship between VC and brand loyalty. The study also identified four consumer groups – attentive group, dedicated group, prospective group and switchers group. Furthermore, consumer classification according to BESC can be used by marketers and managers in marketing strategy development. Originality/value: The study has originality and value in developing and testing a new model linking BESC with VC and brand loyalty. Further, market segmentation on the basis of BESC and VC has been rarely studied. Even less, has been studied among Generation Z consumers and this study fills this important gap.